Dendrimer-assisted formation of fluorescent nanogels for drug delivery and intracellular imaging - Gonçalves, Mara (2019)
Although, in general, nanogels present a good biocompatibility and are able to mimic biological tissues, their unstability and uncontrollable release properties still limit their biomedical applications. In this study, a simple approach was used to develop dual-cross-linked dendrimer/alginate nanogels (AG/G5), using CaCl2 as cross-linker and amine-terminated generation 5 dendrimer (G5) as a cocrosslinker, through an emulsion method. Via their strong electrostatic interactions with anionic AG, together with cross-linker Ca(2+), G5 dendrimers can be used to mediate the formation of more compact structural nanogels with smaller size (433 ± 17 nm) than that (873 ± 116 nm) of the Ca(2+)-cross-linked AG nanogels in the absence of G5. Under physiological (pH 7.4) and acidic (pH 5.5) conditions, the sizes of Ca(2+)-cross-linked AG nanogels gradually decrease probably because of their degradation, while dual-cross-linked AG/G5 nanogels maintain a relatively more stable structure. Furthermore, the AG/G5 nanogels effectively encapsulate the anticancer drug doxorubicin (Dox) with a loading capacity 3 times higher than that of AG nanogels. The AG/G5 nanogels were able to release Dox in a sustained way, avoiding the burst release observed for AG nanogels. In vitro studies show that the AG/G5-Dox NGs were effectively taken up by CAL-72 cells (a human osteosarcoma cell line) and maintain the anticancer cytotoxicity levels of free Dox. Interestingly, G5 labeled with a fluorescent marker can be integrated into the nanogels and be used to track the nanogels inside cells by fluorescence microscopy. These findings demonstrate that AG/G5 nanogels may serve as a general platform for therapeutic delivery and/or cell imaging.